2022
DOI: 10.3390/ijms231911187
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Appropriate Reference Genes for qRT–PCR Normalization in Oat (Avena sativa L.) under UV-B and High-Light Stresses

Abstract: Oat is a food and forage crop species widely cultivated worldwide, and it is also an important forage grass in plateau regions of China, where there is a high level of ultraviolet radiation and sunlight. Screening suitable reference genes for oat under UV-B and high-light stresses is a prerequisite for ensuring the accuracy of real-time quantitative PCR (qRT–PCR) data used in plant adaptation research. In this study, eight candidate reference genes (sulfite oxidase, SUOX; victorin binding protein, VBP; actin-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…RefFinder assigns appropriate weights to the results of candidate RGs in each program based on the GeNorm, NormFinder, BestKeeper, and Delta-Ct algorithms, and then performs stability ranking by calculating the geometric mean of the stability value weights of all algorithms. Because of its comprehensive analysis advantage, this method is increasingly being used in RG studies [42,43]. In our study, eIF5A ranked highly in leaves under different temperature stresses, leaves of plants at different growth stages, and different organs, and consistent results were obtained in RefFinder.…”
Section: Discussionsupporting
confidence: 75%
“…RefFinder assigns appropriate weights to the results of candidate RGs in each program based on the GeNorm, NormFinder, BestKeeper, and Delta-Ct algorithms, and then performs stability ranking by calculating the geometric mean of the stability value weights of all algorithms. Because of its comprehensive analysis advantage, this method is increasingly being used in RG studies [42,43]. In our study, eIF5A ranked highly in leaves under different temperature stresses, leaves of plants at different growth stages, and different organs, and consistent results were obtained in RefFinder.…”
Section: Discussionsupporting
confidence: 75%
“…To identify these genes, selecting suitable reference genes for qRT-PCR analyses is crucial to avoid misleading results. The expression and stability of any given reference gene could vary greatly under different experimental conditions [ 17 , 18 , 19 ]. Consequently, several studies have identified experiment-specific reference genes in various plant species [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression and stability of any given reference gene could vary greatly under different experimental conditions [ 17 , 18 , 19 ]. Consequently, several studies have identified experiment-specific reference genes in various plant species [ 18 , 19 ]. Despite this progress across numerous plant species, it is surprising that a suitable reference gene in M. officinalis has never been established, in any experimental condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in different tissues of Isatis indigotica , CYP was the most stable reference gene [ 41 ], but in all samples of Lycoris aurea , the stability of the CYP gene was poor [ 42 ]. The most stably expressed reference genes in the roots, stems, and leaves under high-light stress were PSKS1 , UBC2 , and PSKS1 , respectively [ 43 ]. The EF-1α gene was identified as an unstable reference gene in response to herbicide stress in wild oat [ 44 ].…”
Section: Discussionmentioning
confidence: 99%